Bending mechanism for piezoelectric transducer footstep energy harvesting using piezoelectric tile - Mohd Asry, Anis Maisarah (2021)
The technologies for energy harvesting technologies using human body action have attracted much attention as alternative resource to replace the common energy resources that have been exhausted in these few decades. Piezoelectric material that has been widely used in sensor technologies is able to produce electrical energy from mechanical energy. Therefore, this transducer can be used to harvest the wasted mechanical energy from human body action. Many researchers use this piezoelectric transducer to harvest the mechanical energy from human footsteps by inserting this transducer in shoes. However, the designated shoes sometimes are not convenient to wearers. In this research, the mechanical energy from the human footstep was harvested using floor tile inserted with piezoelectric transducers. Typically, the output of the piezoelectric transducer is low. Hence a bending mechanism which is divided into two parts, namely support housing and presser was designed to enhance the output piezoelectric transducer in this research. The piezoelectric transducers were connected in a parallel configuration and inserted in the piezoelectric tile together with bending mechanism. The drop test was employed to test this piezoelectric tile with various weight loads and speeds. The highest output power generated was 634.54 μW when 6 kg load was released at 2 drop/sec with 1.89 N average force applied on each piezoelectric transducer. The mechanical energy from the human footstep was intermittent, thus it needed a storage device to store the energy before being used. The full-wave bridge rectifier rectified the output from the piezoelectric tile before being stored in a supercapacitor. The 5.5 V, 1.5 F supercapacitor can be used to charge up to 10.48 V when 60 kg subject pressed the piezoelectric tile with an increment of 60 steps. This tile also can be placed in the ticket counter, walking pavement, dancing floor or exercise instruments to harvest more energy from the footsteps.